Стратегії навчання іноземним мовам майбутніх юристів - Решитько, А. Д.; Reshytko, A. D.; Самойлова, Ю. І.; Samoilova, Yu. I.; Довгополова, Г. Г.; Dovhopolova, H. H.; Юлія Самойлова; Г.Г. Довгополова; Анна Решитько (Актуальнi питання гуманiтарних наук. - 2023. - Вип. 62, т. 2. - С. 279-284, 2023)
Статтю присвячено стратегіям навчання іноземної мови для здійснення професійної діяльності. Наводяться визначення поняття «стратегія навчання», актуалізованого у сфері мовної освіти. Дається класифікація навчальних стратегій з урахуванням принципів компетентнісно-модульної організації навчального процесу. Пропонується виокремлювати такі стратегії навчання бакалаврів англійської мови: мовні, комунікативні, інтегративні творчі стратегії. Дані стратегії рекомендується вважати ефективними для бакалаврату немовного вишу. Стратегії співвідносяться з компетенціями, формуванню яких вони сприяють, і навіть із категорією «уміння». Мовні вміння передбачають накопичення спеціальної термінології за фахом; активне освоєння граматичних конструкцій, притаманних ділового стилю. Комунікативні вміння – це вміння обробляти та інтерпретувати інформацію; володіти мовним етикетом, листуватися англійською; використовувати країнознавчі та культурні фонові знання. Інтегративні вміння полягають у здібностях самостійно знаходити різні джерела інформації іноземною мовою; обробляти, інтерпретувати інформацію; реалізовувати продукт із використанням комунікаційних та інформаційних технологій. Розглядаються питання, пов’язані з організацією навчання через систему вправ. Стратегії, компетенції (уміння) та вправи представлені системно взаємопов’язаними.

Nowadays, there is a need to revise approaches to the training of qualified lawyers in higher education institutions. The issue of students’ autonomy regarding a foreign language and their responsibility for the result of their studies is of particular importance. Discipline learning strategies will help students become more independent, increase their personal interest in learning, and teach self-evaluation and self-correction processes. The article is devoted to foreign language learning strategies for professional activities. Definitions of the term “learning strategy” updated in the field of language education are given. The classification of educational strategies is given taking into account the principles of competence-modular organization of the educational process. It is proposed to single out the following strategies for teaching English language bachelors: linguistic, communicative, integrative creative strategies. These strategies are recommended to be considered effective for bachelors of non-language higher education. Strategies are correlated with the competencies they contribute to, and even with the category of “skills”. Language skills involve the accumulation of special terminology by profession; active learning of grammatical constructions inherent in business style. Communication skills are the ability to process and interpret information; have language etiquette, correspond in English; use country studies and cultural background knowledge. Integrative skills consist in the ability to independently find various sources of information in a foreign language; process, interpret information; implement the product using communication and information technologies. Questions related to the organization of training through a system of exercises are considered. Strategies, competencies (skills) and exercises are presented as systemically interconnected.

Статья посвящена стратегиям обучения иностранному языку для осуществления профессиональной деятельности. Приводятся определения понятия "стратегия обучения", актуализированного в сфере языкового образования. Дается классификация обучающих стратегий с учетом принципов компетентностно-модульной организации учебного процесса. Предлагается выделить следующие стратегии обучения бакалавров английского языка: языковые, коммуникативные, интегративные творческие стратегии. Данные стратегии рекомендуется считать эффективными для бакалавриата неязыкового вуза. Стратегии соотносятся с компетенциями, формированию которых они способствуют, а также с категорией «умения». Речевые умения предполагают накопление специальной терминологии по специальности; активное освоение грамматических конструкций, характерных для делового стиля. Коммуникативные умения – это умение обрабатывать и интерпретировать информацию; владеть языковым этикетом, переписываться на английском; использовать страноведческие и культурные фоновые знания. Интегративные умения состоят в способностях самостоятельно находить различные источники информации на иностранном языке; обрабатывать, интерпретировать информацию; реализовывать продукт с использованием коммуникационных и информационных технологий. Рассматриваются вопросы, связанные с организацией обучения через систему упражнений. Стратегии, компетенции (умения) и упражнения представлены системно взаимосвязанными.
Strategies of learning foreign languages future lawyers
Keywords: стратегія навчання; навчання іноземної мови; навчальні вправи; навчальний процес; компетентнісно-модульна організація; іншомовна професійна діяльність; learning strategy; learning a foreign language; training exercises; competency-modular organization; educational process; foreign language professional activity; стратегия обучения; обучение иностранному языку; учебные упражнения; компетентностно-модульная организация; учебный процесс; иноязычная профессиональная деятельность